2016
DOI: 10.21640/ns.v8i17.522
|View full text |Cite
|
Sign up to set email alerts
|

Dinámica poblacional y aislamiento de bacterias ácido lácticas en lactosuero fermentado

Abstract: Introducción: El consumo de queso producido con leche cruda puede causar daños a la salud debido a la carga microbiana presente en la leche bronca, que puede incluir microorganismos patógenos. Los cultivos iniciadores endémicos de los quesos artesanales podrían mejorar el sabor de quesos fabricados con leche pasteurizada. El objetivo de este trabajo fue estudiar la dinámica poblacional de bacterias ácido lácticas (BAL) del suero fermentado de queso de hebra (SFQH) y su aislamiento.Método: El suero de queso fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Evaluating the microbiological quality of the final fresh cheese product as well as the intermediates throughout the production line is an important contribution to control the quality of the product, as suggested for the production of mozzarella cheese (Losito et al, 2014). In other studies, dynamic populations isolated from whey, from artisan string cheeses manufactured with raw milk, have been reported in the literature (Martínez-López et al, 2016;Moser et al, 2018). Isolates of whey from artisan string cheese showed that Enterococcus and Lactobacillus were the dominant genera (Luiz et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Evaluating the microbiological quality of the final fresh cheese product as well as the intermediates throughout the production line is an important contribution to control the quality of the product, as suggested for the production of mozzarella cheese (Losito et al, 2014). In other studies, dynamic populations isolated from whey, from artisan string cheeses manufactured with raw milk, have been reported in the literature (Martínez-López et al, 2016;Moser et al, 2018). Isolates of whey from artisan string cheese showed that Enterococcus and Lactobacillus were the dominant genera (Luiz et al, 2016).…”
Section: Discussionmentioning
confidence: 89%